2016
DOI: 10.1016/j.ijheatmasstransfer.2015.12.030
|View full text |Cite
|
Sign up to set email alerts
|

A 2D model for coupled heat, air, and moisture transfer through porous media in contact with air channels

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Several recent works demonstrated that the air transfer should not be neglected to ensure the reliability of the model prediction . In Reference , the impact of air transfer was highlighted using an experimental approach. In References , a numerical model, based on a commercial software, was used to investigate the impact of air transfer on the heat and mass transfer in a porous material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent works demonstrated that the air transfer should not be neglected to ensure the reliability of the model prediction . In Reference , the impact of air transfer was highlighted using an experimental approach. In References , a numerical model, based on a commercial software, was used to investigate the impact of air transfer on the heat and mass transfer in a porous material.…”
Section: Introductionmentioning
confidence: 99%
“…Several models from the literature are based on these approaches being constrained by these issues. In References , an implicit numerical model is proposed. To overcome the restrictions, authors simplify the boundary conditions or use linear coefficients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results predicted with the proposed model were positively validated with experimental data. Belleudy et al [9] proposed a computational model capable of accounting for the transfer of moisture and heat across walls of the complex structure and for accompanying leakage air flow between components of the wall. In the model three main phenomena were accounted for, namely vapor diffusion and capillary suction in the porous medium and advective moist air transfer through thin channels.…”
mentioning
confidence: 99%
“…A model of the moisture transfer in the clay brick was developed Allam et al [10]. This model was based on the same driving potentials used in [9].The extended model of moisture and heat transfer in homogeneous porous building materials was presented in [11,12]. It consisted of four transport equations, describing vapor, dry air, liquid moisture, and energy transport.…”
mentioning
confidence: 99%